2021
DOI: 10.3390/life12010017
|View full text |Cite
|
Sign up to set email alerts
|

The Basolateral Amygdala Mediates the Role of Rapid Eye Movement Sleep in Integrating Fear Memory Responses

Abstract: The basolateral amygdala (BLA) mediates the effects of stress and fear on rapid eye movement sleep (REM) and on REM-related theta (θ) oscillatory activity in the electroencephalograph (EEG), which is implicated in fear memory consolidation. We used optogenetics to assess the potential role of BLA glutamate neurons (BLAGlu) in regulating behavioral, stress and sleep indices of fear memory, and their relationship to altered θ. An excitatory optogenetic construct targeting glutamatergic cells (AAV-CaMKIIα-hChR2-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 66 publications
(121 reference statements)
1
8
0
Order By: Relevance
“…Of these regions, the amygdala becomes activated and shows local synthesis of pro-inflammatory cytokines shortly after systemic immune challenge with administration of bacterial lipopolysaccharide ( Engler et al, 2011 ; Prager et al, 2013 ). Furthermore, our work has amply demonstrated that it regulates the effects of footshock stress and fear memories on sleep ( Liu et al, 2009 , 2011 ; Wellman et al, 2013 , 2014 , 2016 ), and, more recently, that it mediates the effects of controllable and uncontrollable stress on the neuroimmune system [Unpublished Results] and that its regulation of fear memory may be dependent on REM during the consolidation period ( Machida et al, 2021a , Machida et al, 2021b ). In summary, available evidence indicates that the complex interactions of the immune system, sleep and stress can be explored at functional, mechanistic and neurocircuit levels in ways that can lend new insight into adaptive and maladaptive stress responses.…”
Section: Stressmentioning
confidence: 99%
“…Of these regions, the amygdala becomes activated and shows local synthesis of pro-inflammatory cytokines shortly after systemic immune challenge with administration of bacterial lipopolysaccharide ( Engler et al, 2011 ; Prager et al, 2013 ). Furthermore, our work has amply demonstrated that it regulates the effects of footshock stress and fear memories on sleep ( Liu et al, 2009 , 2011 ; Wellman et al, 2013 , 2014 , 2016 ), and, more recently, that it mediates the effects of controllable and uncontrollable stress on the neuroimmune system [Unpublished Results] and that its regulation of fear memory may be dependent on REM during the consolidation period ( Machida et al, 2021a , Machida et al, 2021b ). In summary, available evidence indicates that the complex interactions of the immune system, sleep and stress can be explored at functional, mechanistic and neurocircuit levels in ways that can lend new insight into adaptive and maladaptive stress responses.…”
Section: Stressmentioning
confidence: 99%
“…Brief optic activation of the basolateral amygdala during REM sleep immediately reduced REM-θ without affecting overall amount of, and propensity for, sleep, whereas optic inhibition increased REM-θ [43,45]. The reduction in REM-θ amplitude was associated with subsequent attenuated freezing and altered fear-conditioned REM-sleep responses [43]. Stimulation during NREM sleep did not affect any output measures, suggesting that the effects were REM-sleep specific.…”
mentioning
confidence: 91%
“…Recent work has shown that the amygdala also regulates REM sleep-specific acitivity that appears important for emotional learning. For example, REM-dependent physiological events, including θ coherence [42], REM-θ amplitude [21,43], and phasic pontinewaves (P-waves, pontine component of PGO waves) [44] may be more accurate predictors of successful consolidation of fear memory than is the amount of REM sleep. Both REM-θ [43,45] and P-waves [37,46,47] are regulated by the amygdala, which, along with the medial prefrontal cortex and hippocampus, exhibits coordinated θ activity associated with contextual fear conditioning [48].…”
mentioning
confidence: 99%
See 2 more Smart Citations